TRANSFORMING FUTURES THROUGH EARLY CHILDHOOD EDUCATION: A MULTIDIMENSIONAL APPROACH - Dr. Aadil Hussain Mir; Mr. Aman Bishnoi (RADJA PUBLIKA, 2026)
Early Childhood Education (ECE) constitutes a critical foundation for lifelong learning, human development, and social well-being. The early years of life, typically spanning from birth to eight years, are marked by rapid neurological growth and heightened responsiveness to environmental influences. This book chapter presents a comprehensive examination of Early Childhood Education by situating it within historical, theoretical, pedagogical, and policy-oriented perspectives. Drawing upon established developmental theories and contemporary research, the chapter highlights the role of quality early learning experiences in fostering cognitive, social, emotional, and physical development. It further explores child-centered pedagogical practices, curriculum design, assessment approaches, and the integral roles of teachers and families in early learning environments. The chapter also critically addresses persistent challenges such as inequitable access, inadequate teacher preparation, limited resources, and gaps between policy and practice. Emphasis is placed on the long-term educational and socio-economic benefits of investing in Early Childhood Education. The chapter concludes by underscoring the necessity of sustained policy commitment, professional development, and inclusive practices to strengthen Early Childhood Education systems and promote equitable developmental outcomes for all children.